Effective Communication among Religious Followers in Balangbuki, Tonasa Village, Tombolo Pao District, Gowa Regency - Ikhwan, Muh; Tike, Arifuddin; Tajibu, Kamaluddin (Jurnal Mercusuar, 2021)
Respect and mutual respect are steps in creating good social relationships in society, especially in the context of different religious communities that differ culturally. Respect and mutual respect should be the basic principle in daily life, so that a harmonious life can be created. A harmonious society will be far from various potential conflicts. However, conflict is also considered a fundamental social fact. This means that conflict will always accompany social life. To neutralize the potential for conflict among religious communities, effective communication is needed to create good social relationships. This study is a type of qualitative phenomenological research that will clarify the type of research. Phenomenology seeks to objectively reveal facts through observation of all designated informants. The phenomenological approach explains and reveals the meaning of experiences based on individual consciousness during living with different religions in Balangbuki. This research was conducted in a natural situation, so there are no limits in interpreting or understanding the phenomena under study. The results of this study show the five basic principles of effective communication among religious communities in Balangbuki, namely, The 5 Inevitable Laws of Effective Communication: Respect, Empathy, Audible, Clarity, and Humble (REACH), as the basic principle in communication. Thus, good social relationships are created, mutual respect is established, help and familiarity are maintained, peaceful and harmonious living is achieved, and religious tolerance is created.